Sub-Zonal versus intracytoplasmic injection produces a higher rate of cloned caprine-bovine interspecies blastocysts - Abdullah, Ramli; Khadijah, W.E.W.; Soh, H.H. (2012)
The production of cloned-caprine embryos using the intraspecies somatic cell nuclear transfer (SCNT) technique is limited by the low source of caprine oocytes as the recipient cytoplasts in certain countries. Therefore, using bovine oocytes as recipient cytoplasts in interspecies somatic cell nuclear transfer (iSCNT), is an alternative approach to produce a large number of cloned-caprine embryos and subsequently offspring at a rapid rate. The aim of this research was to compare the effect of nuclear transfer methods on iSCNT cloned embryos' developmental competence, involving: (a) an intracytoplasmic injection (ICI), and (b) the sub-zonal injection with electrofusion (SUZI), using fetal fibroblast cells as donor karyoplasts. The bovine ovaries were collected from local abattoir and transported to the laboratory within 2-3 h in NaCl (0.9%). The oocytes (n = 725) were recovered by checker-board slicing of the entire surface of the ovary, inside a culture dish, using a razor blade. After slicing, the cumulus-oocyte complexes (COCs) were recovered and selected under a stereomicroscope. Oocytes with several compact layers of cumulus cells were selected and cultured in in vitro maturation (IVM) medium for 20-22 h. After maturation, COCs were denuded in hyaluronidase (0.1%) to remove the cumulus cells. The matured oocytes (with extrusion of first polar body) were selected for enucleation to remove the spindle. Caprine-fetal fibroblast cells (donor karyoplasts) were harvested and transferred to enucleated bovine oocytes, by using either an intracytoplasmic injection or sub-zonal injection, with electrofusion. The injected/fused oocytes were activated and the reconstructed couplets were cultured in KSOM medium for in vitro embryo development in a CO2 (5%) incubator, at 38.5 degrees C in a humidified atmosphere for 8-9 days. The culture medium was changed every 2 days of IVC. The percentage of cleaved embryos and blastocyst formation following sub-zonal injection, with electrofusion was higher than for oocytes which underwent intracytoplasmic injection (60.2% vs. 54.1% and 12.1% vs. 4.5%, respectively). In summary, the nuclear transfer using both methods of sub-zonal injection and intracytoplasmic injection showed satisfactory results - with the former method being apparently higher in in vitro developmental competence in both cases. In conclusion, using caprine-bovine iSCNT to produce caprine embryos and offspring may offer a new approach to increase genetically superior goat populations at a rapid rate to meet the goat meat and milk demand for the industry - especially in the developing countries. (C) 2012 Elsevier B.V. All rights reserved.